Detergent to Mortality Level and Structural Damage of Gill Tissues on Nila Fish (Oreochromis niloticus L.) - Mustofa Niti Suparjo (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2010)
Nila fish (O. niloticus) is one of important commodity of fishery in Indonesian freshwater. One of effort to obtain the satisfying result in this activity was supported with good quality of water condition. The large volumes of detergent used, as cleanser in society, have the potential of happening contamination in aquatic environment. Condition of territorial water which progressively deteriorate will influence the organism which live in it.The aims of this research was to know influence of surfactan detergent  (LAS) Linear Alkylbenzena Sulfonat to mortality level and structural damage of gill tissues on Nila fish (O. niloticus). The method which is used is a laboratory experiment using a completely randomised design consisting of 5 treatments and 3 replicates for each treatment. Result of antecedent test is value float for from LAS with the concentration equal to 100 mg/L, while sill of under detergent concentration is   10 mg/L. At continuation research, by using analysis probit indicated that the value of LC50-96 hours surfactan on Nila fish equal to 8,716 mg/L. While from perception result microscopicly indicate that happened the change at network of gill of Nila fish (O. niloticus) that is hiperplasia, lamellar fusion, hemorrhagi and atrofi. From the research result can be concluded that detergent have an effect into mortality and also structural damage of gill tissues as important organ of respiration at Nila fish (O. niloticus). Excelsior of detergent concentration hence mortality of Nila fish excelsior also. Key Word : Detergent; Nila Fish; Mortality; Gill Damage.